Evolution of Australian Percutaneous Coronary Intervention (from the Melbourne Interventional Group [MIG] Registry) - Yeoh, J.; Yudi, M.; Andrianopoulos, N.; Yan, B.; Clark, D.; Duffy, S.; Brennan, A.; New, G.; Freeman, M.; Eccleston, D.; Sebastian, M.; Reid, Christopher; et al. (Excerpta Medica, Inc, 2017)
Percutaneous coronary intervention (PCI) continues to evolve with shifting patient demographics, treatments, and outcomes. We sought to document the specific changes observed over a 9-year period in a contemporary Australian PCI cohort. The Melbourne Interventional Group is an established multicenter PCI registry in Melbourne, Australia. Data were collected prospectively with 30-day and 12-month follow-ups. Demographic, procedural, and outcome data for all consecutive patients were analyzed with a year-to-year comparison from 2005 to 2013. National Death Index linkage was performed for long-term mortality analysis; 19,858 procedures were captured over 9 years. Patient complexity and acuity increased with a higher proportion of traditional risk factors and more elderly patients who underwent PCI. Angiographic lesion complexity increased with more multivessel coronary artery disease and more American College of Cardiology/American Heart Association type B2/C lesions proceeding to PCI. The 30-day rate of death, myocardial infarction, or target vessel revascularization has not changed nor has 12-month mortality, myocardial infarction, or major adverse cardiovascular event rates. The strongest independent predictor of long-term mortality was cardiogenic shock at presentation (hazard ratio [HR] 2.95, p <0.01). Drug-eluting stent use (HR 0.83, p <0.01) and a history of dyslipidemia (HR 0.81, p <0.01) were associated with long-term survival. In conclusion, from 2005 to 2013, we observed a cohort of higher risk clinical and angiographic characteristics, with stable long-term mortality.